Enriching Local Patterns with Multi-Token Attention for Broad-Sight Neural Networks - Kang, Hankyul; Ryu, Jongbin (Proceedings - 2025 IEEE Winter Conference on Applications of Computer Vision, WACV 2025, 2025)
In neural networks, recognizing visual patterns is challenging because global average pooling disregards local patterns and solely relies on over-concentrated activation. Global average pooling enforces the network to learn objects regardless of their location, so features tend to be activated only in specific regions. To support this claim, we provide a novel analysis of the problems that over-concentration brings about in networks with extensive experiments. We analyze the over-concentration through problems arising from feature variance and dead neurons that are not activated. Based on our analysis, we introduce a multi-token attention pooling layer to alleviate the over-concentration problem. Our attention-pooling layer captures broad-sight local patterns by learning multiple tokens with the proposed distillation algorithm. It resolves the high bias and high variance errors of learned multi-tokens, which is crucial when aggregating local patterns with multi-tokens. Our method applies to various vision tasks and network architectures such as CNN, ViT, and MLP-Mixer. The proposed method improves baselines with few extra resources, and a network employing our pooling method works favorably against state-of-the-art networks. We open-source the code at https://github.com/Lab-LVM/imagenet-models.
Keywords: Bias and variance; Bias-and-variance-error; Learn+; Local patterns; Multi tokens; Multi-token attention pooling; Neural-networks; Over-concentration; Variance error; Visual pattern; bias-and-variance-error; multi-token attention pooling; over-concentration